Policies and programmes to improve preconception nutrition in South Asia - Avishek Hazra; Tashi Choedon; Monica Shrivastav; Raj Kumar Verma; Cheshta Gulati; Dhammica Rowel; Abner Daniel; Preetu Mishra; Naveen Paudyal; Naureen Arshad; Muhammad Salman; Wisal Khan; et al. (The Lancet Regional Health - Southeast Asia)
Summary: The health and health behaviours of women before conception significantly influence maternal and child health outcomes. Despite growing evidence supporting preconception nutrition care, data on the implementation of related policies and programmes remains limited. This paper reviews public policies and programmes delivering preconception nutrition interventions in eight South Asian countries, targeting married pre-pregnant women aged 15–49 years and identifies the systems bottlenecks in programme implementation. Most countries, except Sri Lanka, lack universal programmes for health and nutrition screening, provision of essential micronutrients, counselling on healthy eating and treatment for at-risk women. Even in countries, where supportive policies exist, implementation of comprehensive nutrition services for pre-pregnant women faces significant bottlenecks across six health system building blocks. Addressing these barriers is critical to improving intervention effectiveness, programme implementation, and informed decision-making. Further testing of a proposed comprehensive algorithm for preconception nutrition in diverse country contexts across South Asia is necessary.